Long-Term Performance of Flexible Pavements Constructed on Recycled Base Layers. Issue 11 (November 2022) - Titi, Hani; Qamhia, Issam I. A.; Ramirez, Jessie; Tabatabai, Habib
There has been an increased interest in using reclaimed asphalt pavement (RAP) aggregates as a base course in Wisconsin for the offered economic and environmental benefits. Laboratory studies showed that RAP can have resilient modulus values higher than typical natural aggregates, and can also have higher durability, especially in freeze–thaw cycles. However, it is also recognized that RAP exhibits temperature sensitivity and larger permanent deformations than natural aggregates. How these characteristics manifest themselves in the northern U.S. climates can only be assessed by long-term observation of field performance. Wisconsin Department of Transportation (WisDOT) has been using RAP as a base course for over 30 years. The qualitative assessment of WisDOT roads constructed with RAP showed they are performing adequately. However, this impression has not yet been verified quantitatively. This paper presents a quantitative assessment and comparisons for field performance of pavement test sections constructed with RAP and natural crushed aggregate (CA) base course layers in Wisconsin. The performance was evaluated using pavement distress surveys of roadways containing RAP and CA, falling weight deflectometer (FWD), dynamic cone penetrometer (DCP) tests, and analysis of WisDOT's available data. Based on the field evaluation, the performance of the hot mix asphalt (HMA) pavements with RAP was found adequate and comparable to those with CA base course layers. A recommendation was given that WisDOT shall continue the practice of using RAP in base course layers of HMA pavements, given proper quality checks for materials, and proper quality control/quality assurance measures being applied during construction.